2017
DOI: 10.1080/00140139.2017.1369583
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mental workload with the NASA-TLX needs to examine each dimension rather than relying on the global score: an example with driving

Abstract: The distinction between several components of mental workload is often made in the ergonomics literature. However, measurements used are often established from a global score, notably with several questionnaires that originally reflect several dimensions. The present study tested the effect of driving situation complexity, experience and subjective levels of tension and alertness on each dimension of the NASA-TLX questionnaire of workload, in order to highlight the potential influence of intrinsic, extraneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 45 publications
3
44
0
Order By: Relevance
“…However, it can also be argued that the NASA TLX as an overall value is not sufficiently suitable to distinguish between underutilisation and overstrain. Galy et al [27] have found similar results in a study and therefore suggest to consider the dimensions of the NASA TLX individually. This shows that the NASA score in solo driving is mainly caused by a high effort of the test persons, which differs significantly from the other test rides, although objectively the physical as well as mental effort is lowest.…”
Section: Rq1supporting
confidence: 52%
“…However, it can also be argued that the NASA TLX as an overall value is not sufficiently suitable to distinguish between underutilisation and overstrain. Galy et al [27] have found similar results in a study and therefore suggest to consider the dimensions of the NASA TLX individually. This shows that the NASA score in solo driving is mainly caused by a high effort of the test persons, which differs significantly from the other test rides, although objectively the physical as well as mental effort is lowest.…”
Section: Rq1supporting
confidence: 52%
“…Studies have suggested that a 4-item NASA-TLX may be more suitable for measuring nurse workload, however there is still controversy regarding the application of 4-item or 6-item versions of NASA-TLX in the clinical setting (Galy et al, 2018;Charles et al, 2019). Our current study utilized the 6-item version of NASA-TLX in order to assess different aspects of nurse workload.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that factors such as an increased workload, interruptions, level of personal experience, and stress have the ability to in uence mental workload, which can subsequently have an impact on nurses' critical decision making and patients' safety (Happell et al, 2013). However, ergonomics studies have suggested that the measurement of mental workload using the NASA-TLX requires taking into account each of its individual dimensions, rather than simply assessing of the global score (Galy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…121 The NASA TLX assesses workload across six subscales; Mental Demand, Physical Demand, Temporal Demand, Performance, Effort and Frustration. 119 Participants completed this assessment via the NASA TLX software application (NASA, Washington DC, Washington) on a provided Apple iPad (Apple Inc, Cupertino, California, USA). Participants will be presented with 15 questions which compared the six subscales and asked to circle which subscale was most influential during the driving task.…”
Section: Driving Simulatormentioning
confidence: 99%